Some Aspect Biology Reproduction of the Indonesian Predatory Catfish (Wallagonia leerii Bleeker, 1851) in Sebangau River Central Kalimantan - Riza, Nurasiah; Butet, Nurlisa Alias; Kamal, Mohammad Mukhlis; Wibowo, Arif; Simon, Okta; Ansori, Ma'mun (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Tapah fish (Wallagonia leerii) is one of the economically valuable and popular fish species because its large size and make it the main target for fishing in the Sebangau River. It is feared that excessive exploitation of these fish can cause a decline and threaten the sustainability of tapah fish, which up to now still depend on nature. This research aimed to describe reproductive biology of tapah fish related to sex ratio, gonad maturity, gonado-somato index and fecundity. A total of 96 fish samples were collected using fishing trap and seine net for three months at five sampling sites in Sebangau River. The results showed that the sex ratio of male and female for all samples were 1:0.9 and Chi-square test with a 95% confidence interval showed approaching to 1:1 ratio. The GSI value of male and female ranged from 0,110% – 0,522% and 0,112% – 0,651%. The spawning times were recorded from Desember to January. The total fecundity of 11 female ranged from 2976 to 155501 eggs with an average of 43334 eggs.